Розробка ігрового рівня гри та прототипування його механік - Чорненький, О. В. (ХНУРЕ, 2025)
Despite the strong potential of Ukrainian developers, the number of popular game projects created in Ukraine remains insufficient. This indicates the need to intensify efforts to improve the quality and competitiveness of Ukrainian games. During the work, it was decided to do a project to prototyping game mechanics without creating additional 3D models and textures, and instead use the built-in and free Unreal Engine 5 libraries.
Keywords: розробка гри; Ukrainian games